Development Student’s Writing Skill Through Blended Learning Model - Isnaini Ramadaniah; Harianto II (PT Inovasi Pratama Internasional, 2023)
This research aims (1) To develop student’s writing skill through blended learning (2) To find out whether blended learning can develop student’s writing skills through blended learning. (3) To explain the process of developing writing skills using blended learning. The population of the research was the students of STKIP Usman Safri Kutacane. The sample was second semester consisted of 12 students. The sample was taken by purposive sampling. The research was a Research and Experimental Development (R&D), which conducted by giving two tests, pre-test and post-test. Pre-test was given before implementing writing descriptive essay while post-test was given after implementing writing descriptive essay. It was carried out on using qualitative and quantitave method. The instrument of the data collection was a essay writing tests.. The data was analyzed by using T-test. After the data had been collected by using test, it was found that the pre-test average was 61,67 while post-test was 76,67. There were 15% improvement from the pre-test value. So, the writer concluded that there were improvement of the writing skill of the students through blended learning model. It can also proved by comparing the result t observation (5,169) with t table (4,318) for alpha = 0,1%. It was meant that the hypothesis was received.